2014
DOI: 10.1680/stbu.12.00029
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency factors of recycled concrete bottle-shaped struts

Abstract: Reported test results of reinforced concrete beams made with coarse recycled concrete aggregate have been re-analysed using strut-and-tie models and the efficiency factors of the recycled concrete aggregate concrete bottle-shaped struts compared with those made of natural coarse aggregate. The objective was to ascertain whether strut-and-tie model provisions for efficiency factors of bottle-shaped struts in current design codes and the recent literature, originally meant for natural coarse aggregate concrete, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…According to Hohanson's studies [34,35], it can be found that particle shape has great influence on the material mechanical properties and failure modulus. Therefore, in order to better reveal the influence of coarse aggregate on the elastic modulus of concrete, it is necessary to quantify the geometric features of coarse aggregate.…”
Section: Identification For Concrete Modelmentioning
confidence: 99%
“…According to Hohanson's studies [34,35], it can be found that particle shape has great influence on the material mechanical properties and failure modulus. Therefore, in order to better reveal the influence of coarse aggregate on the elastic modulus of concrete, it is necessary to quantify the geometric features of coarse aggregate.…”
Section: Identification For Concrete Modelmentioning
confidence: 99%
“…The third paper, by Sahoo et al (2014), investigates the efficiency factors of recycled concrete bottle-shaped struts compared with those made of natural coarse aggregate in current design codes. The comparisons show that the ACI 318-08 (ACI, 2008) provisions give unsafe efficiency factor predictions for all beams considered, whereas Eurocode 2 (BSI, 2004) strut efficiency factors are found to be unsafe in some cases.…”
mentioning
confidence: 99%